Symphonies 1-9 Ludwig van Beethoven's 9 Symphonies - Beethoven, Ludwig Ĉvanĉ; Schwarzkopf, Elisabeth; Haefliger, Ernst; Edelmann, Otto; Hèoffgen, Marga; Karajan, Herbert Ĉvonĉ (ZYX Music, 2014)
Enth.: Sinfonie Nr. 1 op. 21, Sinfonie Nr. 3 op. 55; Sinfonie Nr. 2 op. 36, Sinfonie Nr. 7 op. 92; Sinfonie Nr. 4 op. 60, Sinfonie Nr. 5 op. 67, Ouvertèure Coriolan op. 62; Sinfonie Nr. 6 op. 68 "Pastorale", Sinfonie Nr. 8 op. 93, Ouvertèure Egmont op. 84; Sinfonie Nr. 9 op. 125 "Choral"; mit Elisabeth Schwarzkopf, Marga Hèoffgen, Ernst Haefliger, Otto Edelmann.